Revisiting Al-Ghazali’s Thought: Contemporary Integration of Islamic Spirituality and Economics for Community Development - Nurlinda (NUSANTARA: Journal Of Law Studies, 2024)
This study revisits the thought of Imam Al-Ghazali to explore the contemporary integration of Islamic spirituality and economics as a comprehensive foundation for sustainable community development. Al-Ghazali’s intellectual legacy presents a holistic framework that harmonizes material welfare with spiritual growth, asserting that economic activity is an ethical and spiritual act oriented toward maslahah (public good) and taqwa (God-consciousness). Using a qualitative-descriptive method through a library-based and hermeneutic analysis, this research critically examines Al-Ghazali’s principal works—particularly Ihya’ ‘Ulum al-Din and al-Mustasfa—to reinterpret his economic and spiritual insights within the context of contemporary socio-economic challenges. The findings indicate that Al-Ghazali’s economic thought is anchored in the principles of maqasid al-shariah (the higher objectives of Islamic law), promoting balance between spiritual purification (tazkiyah al-nafs), justice (‘adl), and productive engagement (kasb). This integration reinforces the notion that the ultimate goal of economic development is not material accumulation, but the realization of human well-being (falah) through moral discipline and social equity. In the modern era, Al-Ghazali’s paradigm offers a transformative perspective to counteract moral decline, inequality, and materialism in global economic systems. Academically, this research contributes to the advancement of Islamic economic thought and spiritual ethics by reconstructing Al-Ghazali’s framework into a contemporary paradigm of integrative community development. It bridges classical Islamic scholarship with modern development discourse, offering a values-based model that aligns economic empowerment with ethical responsibility. Furthermore, the study provides a theoretical foundation for future interdisciplinary research linking Islamic spirituality, socio-economic justice, and sustainable development.